Legal Antropology Approach on The Application of Village Website in Digital Economic Era in Indonesia - Sarip Sarip; Diana Fitriana (Universitas Kuningan, 2018)
Legal anthropology approach is a scientific discipline which explicitly focuses on normative complexity in society and on the relationship between human behavior and its complexity and changes in both human behavior and normative complexity. The application of modern technology in villages has shown the central governments support, especially in the acceleration of village economy. On the other hand, there are not many people in the village who understand the application of the technology itself. Villages, that are vulnerable to changes, require special attention especially with regard to technology. The aim of legal anthropology in accelerating the digital economy is expected to provide a balance in the acceleration of village economy. Thus, the issue raised in this research is how the novelty and renewal of law on digital economy acceleration through the village website viewed from legal anthropology. This research used a normative legal research method which was done by describing views related to the subject matter. In terms of anthropological tendency, there is a tendency adjusted to the dynamics of the societys culture including the acceleration of digital economy for the village. Anthropology sees only law as an aspect of culture, namely an aspect used by public authority in regulating behavior and society, so that there are no deviations and irregularities of the determined social norms. Legal anthropology looks at possible differences or even conflicts in order to assess the modernization culture with the level of understanding in the village. The legal novelty and renewal in the village with regard to digital economic acceleration is considered as a channel, means, and a type of membrane that can be penetrated without disturbing or damaging the membrane.Pendekatan Antropologi hukum merupakan disiplin ilmiah yang paling eksplisit memusatkan perhatian pada ke-kompleksitasan normatif dalam masyarakat dan pada hubungan antara prilaku manusia dengan ke-kompleksitasan, perubahan-perubahan baik dalam prilaku manusia maupun dalam kekompleksitasan normatif. Penerapan teknologi modern di desa- desa telah menunjukan dukungan pemerintah pusat terutama dalam percepatan ekonomi desa. Di sisi lain masyarakat desa masih belum banyak yang mengerti akan penerapan teknologi itu sendiri. Desa yang rentan akan perubahan memerlukan perhatian yang khusus apalagi berkenaan dengan teknologi. Tujuan antropologi hukum dalam percepatan ekonomi digital diharapkan memberikan keseimbangan dalam percepatan ekonomi desa. Maka yang menjadi pertanyaan yakni bagaimana kebaruan dan pembaharuan hukum percepatan ekonomi digital melalui website desa dilihat dari sisi antropologi hukum. Penelitian sendiri menggunakan metode penelitian hukum normative dilakukan dengan cara mendeskripsikan pemikiran yang berkenaan dengan pokok bahasan. Kecenderungan antropologis, terdapat kecenderungan yang disesuaikan dengan dinamika budaya masyarakat termasuk didalamnya percepatan ekonomi digital bagi desa. Antropologi melihat hukum sebagai aspek dari kebudayaan, yaitu suatu aspek yang digunakan oleh kekuasaan masyarakat yang teratur dalam mengatur perilaku dan masyarakat, agar tidak terjadi penyimpangan dan penyimpangan yang terjadi dari norma-norma sosial yang ditentukan dapat diperbaiki.Antropologi hukum dengan melihat kemungkinan perbedaan atau bahkan pertentangan masyarakat desa dalam rangka menilai budaya modernisasi dengan tingkat pemahaman di desa.Kebaruan dan pembaharuan hukum di desa berkenaan dengan percepatan ekonomi digital dianggap sebagai saluran, sarana, sejenis selaput yang bisa ditembus tanpa mengganggu atau merusak selaput.